Propolis increases Foxp3 expression and lymphocyte proliferation in HIV-infected people: A randomized, double blind, parallel-group and placebo-controlled study - Conte, Fernanda Lopes [UNESP]; Tasca, Karen Ingrid [UNESP]; Santiago, Karina Basso [UNESP]; de Oliveira Cardoso, Eliza [UNESP]; Romagnoli, Graziela Gorete [UNESP]; de Assis Golim, Marjorie [UNESP]; Braz, Aline Márcia Marques [UNESP]; Berretta, Andresa Aparecida; do Rosário de Souza, Lenice [UNESP]; Sforcin, José Maurício [UNESP] (Elsevier, 2021)
HIV infection and the prolonged use of antiretroviral therapy (ART) contribute to persistent inflammation and immune deregulation in people living with HIV/AIDS (PLWHA). Propolis is a bee product with plenty of biological properties, including immunomodulatory and anti-inflammatory action. This work aimed to evaluate possible changes in the immune/inflammatory response in PLWHA under ART after propolis intake. Asymptomatic PLWHA were double-blindly randomized into parallel groups receiving propolis (500 mg/day, n = 20) for 3 months or placebo (n = 20). Plasma cytokines (TNF-α, IL-2, IL-4, IL-6, IL-10 and IL17) were evaluated by cytometric bead array; cytokine production by PBMC (IFN-γ, IL-5, IL-17, IL-10, IL-1β, IL-18, and IL-33) was assessed by ELISA; gene expression (T-bet, GATA-3, RORγt and Foxp3) was determined by RT-qPCR, and cell proliferation was analysed by flow cytometry using CFSE staining. The average of gender, age, CD4+/CD8+ T cell count, time of diagnosis and treatment were similar in both groups. No differences were observed in cytokine levels nor in inflammasome activation. However, Pearson's correlation showed that IL-10 was directly correlated to CD4+ T cell count and inversely to IFN-γ after treatment with propolis. Foxp3 expression and lymphocyte proliferation increased in the propolis group. Data suggested that daily propolis consumption may improve the immune response and decrease the inflammatory status in asymptomatic PLWHA under ART.
Keywords: Antiretroviral therapy; HIV/AIDS; Immunomodulation; Inflammation; Propolis; Treg cells